The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1415-65552010000400008
|View full text |Cite
|
Sign up to set email alerts
|

Relações de poder e mudanças pós-aquisição internacional na rede de relacionamentos da adquirida

Abstract: Embasados na perspectiva de redes industriais e na literatura de canais de distribuição, neste artigo analisamos poder e mudanças pós-aquisição internacional, ocorridas nos relacionamentos da adquirida com fornecedores e compradores. Especificamente, investigamos se e como a variável poder influencia mudanças pós-aquisição internacional na rede de relacionamentos da adquirida. Para tanto, desenvolvemos um estudo de caso, com base em entrevistas semiestruturadas com representantes da adquirente, adquirida, forn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…On top of it, this type and direction of change was considered the most important post-acquisition change. Interestingly enough, this finding has not been reported in the literature on M&A at the network level (Havila & Salmi, 2000, even in those empirical studies that place particular emphasis on types of managerial changes that follow M&A (Degbey & Pelto, 2013;Esper et al, 2010;Freitas et al, 2008). As this piece of research is, to our knowledge, the first to delve into the non-economic dimension of post-acquisition changes in acquired firm relationships, we present preliminary evidence that professionalism is a typical noneconomic post-acquisition change beyond the dyad.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…On top of it, this type and direction of change was considered the most important post-acquisition change. Interestingly enough, this finding has not been reported in the literature on M&A at the network level (Havila & Salmi, 2000, even in those empirical studies that place particular emphasis on types of managerial changes that follow M&A (Degbey & Pelto, 2013;Esper et al, 2010;Freitas et al, 2008). As this piece of research is, to our knowledge, the first to delve into the non-economic dimension of post-acquisition changes in acquired firm relationships, we present preliminary evidence that professionalism is a typical noneconomic post-acquisition change beyond the dyad.…”
Section: Discussionmentioning
confidence: 50%
“…As the degree of dependence assumes the role of the dependent variable, here it is suggested that it is a type of change that follows M&A. In this sense, it takes on the role of neither the mediating (Rezende & Duarte, 2004) nor the moderating (Esper et al, 2010;Oberg et al, 2011) variable in M&A at the network level. Based on this, we recommend that future empirical studies should contrast these views in order to shed more light on the role of the degree of dependence in the non-economic dimension of post-acquisition changes in the relationships of the acquired firm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations